THE REPRESENTATION OF THE EAST IN ENGLISH LITERATURE (17TH TO 20TH CENTURIES) - Ozoda Omonaliyeva Lutfulla qizi; Advisor Erkulova Feruza Melikuziyevna (Western European Studies, 2025)
This article delves into the multifaceted representation of the East in English literature from the 17th to the 20th centuries, a period marked by significant socio-political transformations and an expanding British Empire. As England's colonial reach extended into Asia, Africa, and the Middle East, literary portrayals of Eastern cultures emerged as both reflections of fascination and instruments of power. Key authors such as John Milton, Lord Byron, and Rudyard Kipling contributed to a complex Orientalist discourse that oscillated between admiration for Eastern beauty and exoticism, and the perpetuation of stereotypes that reinforced colonial ideologies. This study examines seminal literary works that encapsulate these themes, analyzing how they mirror the broader cultural and historical contexts of their time. By tracing the evolution of these representations over three centuries, this article aims to illuminate the intricate relationship between England and the East, revealing how literature served not only as a medium for exploration but also as a tool for constructing the "Other." Ultimately, this exploration underscores the importance of critically engaging with literary texts to understand their role in shaping perceptions of Eastern cultures throughout history.
Keywords: East; English literature